2000
DOI: 10.1038/sj.bjp.0703169
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of [Nphe1]nociceptin(1‐13)NH2, a new selective nociceptin receptor antagonist

Abstract: 1 Nociceptin (orphanin FQ) is a novel neuropeptide capable of inducing a variety of biological actions via activation of a speci®c G-protein coupled receptor. However, the lack of a selective nociceptin receptor antagonist has hampered our understanding of nociceptin actions and the role of this peptide in pathophysiological states. As part of a broader programme of research, geared to the identi®cation and characterization of nociceptin receptor ligands, we report that the novel peptide [Nphe 1 ]nociceptin(1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
119
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(130 citation statements)
references
References 44 publications
11
119
0
Order By: Relevance
“…Currently available ligands for the NOP receptor and their therapeutic potential have been recently reviewed by Zaveri (2003). These are 1) nonpeptide ligands generally discovered via high-throughput screening in industrial laboratories (e.g., the NOPselective antagonists J-113397 (Ozaki et al, 2000) and SB-612111 (Zaratin et al, 2004); 2) small peptides identified by screening of synthetic peptide combinatorial libraries [e.g., the NOP-selective partial agonist Ac-RYYRWK-NH 2 (Dooley et al, 1997) or the nonselective NOP ligand peptide III-BTD (Becker et al, 1999)]; and 3) N/OFQrelated peptides identified by classical structure activity relationship studies (for review, see Guerrini et al, 2000), including the full agonists N/OFQ(1-13)-NH 2 and N/OFQ-NH 2 (Calo et al, 1996), the partial agonist [Phe 1 ⌿(CH 2 -NH)Gly 2 ]N/OFQ(1-13)-NH 2 , and the pure antagonist [Nphe 1 ]N/OFQ(1-13)-NH 2 (Calo et al, 2000a).…”
mentioning
confidence: 99%
“…Currently available ligands for the NOP receptor and their therapeutic potential have been recently reviewed by Zaveri (2003). These are 1) nonpeptide ligands generally discovered via high-throughput screening in industrial laboratories (e.g., the NOPselective antagonists J-113397 (Ozaki et al, 2000) and SB-612111 (Zaratin et al, 2004); 2) small peptides identified by screening of synthetic peptide combinatorial libraries [e.g., the NOP-selective partial agonist Ac-RYYRWK-NH 2 (Dooley et al, 1997) or the nonselective NOP ligand peptide III-BTD (Becker et al, 1999)]; and 3) N/OFQrelated peptides identified by classical structure activity relationship studies (for review, see Guerrini et al, 2000), including the full agonists N/OFQ(1-13)-NH 2 and N/OFQ-NH 2 (Calo et al, 1996), the partial agonist [Phe 1 ⌿(CH 2 -NH)Gly 2 ]N/OFQ(1-13)-NH 2 , and the pure antagonist [Nphe 1 ]N/OFQ(1-13)-NH 2 (Calo et al, 2000a).…”
mentioning
confidence: 99%
“…In the present study, we found i. 3 ]NC(1-13)NH 2 suggested that the hydrophobicity of the N-terminal tetrapeptide showed no significant effect on the binding and activating activities of NC to OP 4 receptor, but the flexibility of this region seems to play very important roles in the NC-OP 4 receptor interaction. The present work also helps to provide a novel and simplified method to perform structure-activity study, which could investigate the roles of the hydrophobicity and flexibility of defined fragment in the native peptide at the same time through a simple replacement.…”
Section: Discussionmentioning
confidence: 56%
“…Taking NC(1-13)NH 2 as a template, a series of analogues were designed and synthesized to study the structure-activity relationship of the N-terminal tetrapeptide of NC [2,3,6,14]. In an attempt to protect NC(1-13)NH 2 from degradation by aminopeptidases, the pseudopeptide [Phe 1 (CH 2 -NH)Gly 2 ]NC(1-13)NH 2 ([F/G]NC(1-13)NH 2 ) was designed [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…It also acted similarly to nociceptin in a variety of in vivo assays, including its action with respect to analgesic activity (Grisel et al, 1998). However, Calo et al (2000) later described a new peptide analog, [NPhe 1 N/OFQ(1-13)NH 2 ], which was a selective and competitive nociceptin antagonist, devoid of any residual agonist activity.…”
Section: Introductionmentioning
confidence: 99%